Determinan Pengetahuan dan Persepsi Terhadap Minat Menabung di Bank Syariah (Studi Kasus Mahasiswa HES IAIN BATUSANGKAR) - Muhammad Deni Putra; Elimartati; Rizal Fahlefi; Sitri Nofrita Sari (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This research was conducted to examine how students' knowledge of Islamic Bank products, to determine the students' own perceptions of the interest in saving in Islamic banks and to find out whether there is a relationship between the knowledge and perceptions of students majoring in HES on interest in saving at Islamic Banks. This type of research is field research using quantitative methods. The data collection technique that the author uses is through a questionnaire. Data processing is carried out by quantitative methods, then described and presented through effective sentences. Based on the results of the research that the authors obtained, it was found that there was a significant relationship between the knowledge of students majoring in HES and interest in saving in Islamic banks. Based on the results of the regression analysis, the tcount value was 3.722 > ttable = 1.671, while the significance value (sig) was 0.000 <0.05. So it can be concluded that Ho1 is rejected and Ha1 is accepted, meaning that partially the knowledge variable (X1) is significantly related to a very strong positive relationship with interest in saving (Y). Meanwhile, on the perception variable, there is no significant relationship between the perceptions of students majoring in HES and interest in saving in Islamic banks. Based on the results of the regression analysis, the tcount value was 1.903 > ttable = 1.671, while the significance value (sig) was 0.061 0.05. So it can be concluded that Ho2 is rejected and Ha2 is accepted, meaning that partially there is no significant relationship between the perception variable (X2) on interest in saving. So it can be said that there is an insignificant relationship between perception and interest in saving.